The impact of entrepreneurship towards innovation in airport industry: The double mediation framework of strategic alignment and learning orientation - Alsuwaidi, Ali Khalifa Mohamed Salim; Al-Shami, Samer Ali Hussein; Akmal, Suriati (Allied Business Academies, 2021)
Innovation is broadly regarded as highpoint of success and one of the essential factors in highly competitive market and global economy. Many airports are lacking strategic alignment to implement entrepreneurship towards innovation in airport facilities and services. Adding to that the absence of learning orientation in airport projects is one of the hinders to improving innovation performance of airports. This study discussed and analyzed the combined mediating effect of learning orientation and strategic alignment on the relationship between entrepreneurial orientation and innovation performance within the context of airport industry. In addition to that, the direct influence of entrepreneurial orientations on innovation performance was examined. This study broadens the understanding of the phenomenon of entrepreneurial and learning orientation through highlighting the importance of strategic alignment relevant with these concepts. The result of this study showed that entrepreneurial orientation has a direct and indirect effect on innovation performance, while learning orientation and strategic alignment mediates the influence of entrepreneurial orientation towards innovation performance.